A Study of Attenuation of Conducted EMI Generation in a Switching Power Supply Using Filtering Technique - Piyawit Sripodok; Chaiyan Jettanasen (My University, 2015)
This paper studies on the attenuation of conducted electromagnetic interference (EMI) generation in a switching power supply using passive filtering technique. The switching power supply functions with the switching frequency rang up 20 kHz and mostly generates noise in low-and-high frequencies; this leads to EMI problems to electronic and/or electrical devices/equipment. To overcome the problems, electromagnetic compatibility (EMC) regulation should be applied. The EMC standard for conducted emission measurement is principally defined in the frequency range of 150 kHz to 30 MHz. The analysis and experimental results show that by inserting a passive filter to the studied switching power supply, the conducted emission can be reduced in the specified frequency range. The obtained results will be additionally compared with an EMC standard (EN55022 class B) in order to reveal the effectiveness of the applied EMI attenuation technique. Finally, the switching power supply should apply filtering technique in development of electronic and/or electrical devices/equipment.
Keywords: Electromagnetic Compatibility; Electronic filter; Electromagnetic Compatibility and Noise Suppression